Prothrombin Synthesis in Rat Hepatoma H4IIEC3 Cells: Response to the Proposed “Coagulopoietin Factor” - Shah, D V; Engelke, J A; Suttie, J W (Thrombosis and Haemostasis, 1993)
Based on studies in intact animals, the presence of humoral factors, “coagulopoietins”, which regulate the synthesis of vitamin K-dependent plasma proteins has been proposed. These proposed factors are produced in response to vitamin K deficiency, coumarin treatment, or specific antibody depletion of vitamin K-dependent clotting factors. The production of pro-thrombin by rat hepatoma H4IIEC3 cells has now been shown to be dependent on the source of bovine serum in the media. Cells grown in serum from cows treated with dicoumarol produce about 20% more prothrombin in 24 h than those cells grown in control serum. The humoral factor causing this response is present early in the course of dicoumarol treatment, and the increase in prothrombin production is dependent on the amount of serum from a dicoumarol-treated cow in the media. Based on membrane filtration studies, the factor appears to be associated with the protein fraction of serum.